Out-of-plane behavior of innovative infill walls made of autoclaved aereated concrete (AAC) subjected to shake table tests - Giulivo, Marco; Borretti, Giovanbattista; Prota, Andrea; Menna, Costantino (Frontiers in Built Environment, 2023)
Seismic damage affecting non-structural components of buildings (such as infills) can significantly impact the expected economic losses over a structure's service life. Recently, autoclaved aerated concrete (AAC) infills have gained attention in the construction industry due to their lightweight, energy efficiency, and durability. This study investigates the out-of-plane behavior of an innovative AAC infill wall system by means of shake table tests. The wall system is made of low-density AAC units with innovative joints made from polyurethane resin and steel plates for connection to the structural frame. Shake table tests are carried out using artificial accelerograms based on ICBO-AC156, which can reproduce a wide range of interstory drift demand. The study is articulated in three stages: mechanical characterization of the AAC infill wall, shake table tests, and seismic behavior analysis of the wall based on current code requirements. The results demonstrate the effectiveness of the innovative AAC infill wall system in resisting out-of-plane seismic loads, also considering different levels of seismic action, with base accelerations reaching up to 0.80 g.